Cloning, expression, purification, crystallization and X‐ray crystallographic analysis of CofB, the minor pilin subunit of CFA/III from human enterotoxigenic Escherichia coli. Issue 6 (1st June 2015) - Kawahara, Kazuki; Oki, Hiroya; Fukakusa, Shunsuke; Maruno, Takahiro; Kobayashi, Yuji; Motooka, Daisuke; Taniguchi, Tooru; Honda, Takeshi; Iida, Tetsuya; Nakamura, Shota; Ohkubo, Tadayasu
<x xml:space="preserve">Abstract</x> Colonization factor antigen III (CFA/III) is one of the virulence factors of human enterotoxigenic Escherichia coli (ETEC) that forms the long, thin, proteinaceous fibres of type IV pili through assembly of its major and minor subunits CofA and CofB, respectively. The crystal structure of CofA has recently been reported; however, the lack of structural information for CofB, the largest among the known type IV pilin subunits, hampers a comprehensive understanding of CFA/III pili. In this study, constructs of wild‐type CofB with an N‐terminal truncation and the corresponding SeMet derivative were cloned, expressed, purified and crystallized. The crystals belonged to the rhombohedral space group R32, with unit‐cell parameters a = b = 103.97, c = 364.57 Å for the wild‐type construct and a = b = 103.47, c = 362.08 Å for the SeMet‐derivatized form. Although the diffraction quality of these crystals was initially very poor, dehydration of the crystals substantially improved the resolution limit from ∼4.0 to ∼2.0 Å. The initial phase was solved by the single‐wavelength anomalous dispersion (SAD) method using a dehydrated SeMet CofB crystal, which resulted in an interpretable electron‐density map.